ANALISA PRODUKTIVITAS TENAGA KERJA PADA PEKERJAAN MEKANIKAL DAN ELEKTRIKAL (STUDI KASUS REVITALISASI GEDUNG KANTOR CABANG BNI KELAPA GADING, JAKARTA) - Yudha Gusty Wibowo; Adhi Purnomo; Lenggogeni (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2021)
In construction world, the labour’s productivity is one of the determining factors for development project. There are many tools to measure the productivity levels. One of which is by examining LUR (Labour Utilitation Rate) for each worker, that is to explore the labour’s effectivity in running their work. The purpose of this research is for knowing the labour’s productivity rate. This research was conducted on revitalization of BNI branch office at Kelapa Gading, Jakarta. by observing the labours in mechanical and electrical work. LUR observation are carried out based on daily reports of completed mechanical and electrical work.